2021
DOI: 10.3389/fphar.2021.631216
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide Induces Dose-Dependent Lung Injury in Mice via Stimulating Vimentin and NLRP3 Inflammasome Production

Abstract: Recently, the therapeutic importance of the anti-rheumatic drug, leflunomide, has been increased after the involvement of leflunomide in treating other autoimmune diseases and its promising role in retarding human malignancies. Few studies have focused on the safety in human or animals without clear outlining of the pathologic features on target organs. One clinical study related leflunomide with significant pulmonary complications in predisposed individuals. The current study examined the dose-dependent lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although cyclosporine has also been used in combination with corticosteroids at low doses in patients with IPF, its effects have not been significant [69]. Similarly, leflunomide used for the treatment of rheumatoid arthritis has been contradictory in pulmonary fibrosis since it has shown both beneficial and detrimental effects [70,71]. The duality of the effects observed for these drugs in pulmonary fibrosis seems to indicate that their effect is dose dependent; however, more research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although cyclosporine has also been used in combination with corticosteroids at low doses in patients with IPF, its effects have not been significant [69]. Similarly, leflunomide used for the treatment of rheumatoid arthritis has been contradictory in pulmonary fibrosis since it has shown both beneficial and detrimental effects [70,71]. The duality of the effects observed for these drugs in pulmonary fibrosis seems to indicate that their effect is dose dependent; however, more research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…LEFN use for eight weeks resulted in lung injury, and there was a marked increase in lung injury when the dose of LEFN increased. Western blot analysis revealed an increase in α-SMA, vimentin, and collagen 1 in LEFN-treated animals; there was also a dose-dependent increase of the same [ 12 ]. In the later study, elevated levels of inflammatory markers (NLRP3 and interlukin-1) were found in dose-dependent pulmonary toxicities, together with architectural structural distortion [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hepatotoxicity induced by LEFN was linked to mitochondrial dysfunction at the transcript level [ 8 ], oxidative stress [ 9 , 10 ], and unfolded proteins accumulation [ 11 ]. In a recent study, LEFN induced inflammatory reactions and pulmonary toxicity in mice, together with architectural structural distortion [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of lung injury was graded 0-4 on four aspects: 1) alveolar congestion; 2) hemorrhage; 3) infiltration of neutrophils in the alveolar space or blood vessel walls; and 4) thickening of the alveolar walls and/or formation of a transparent film. We searched for 3 observers with a certain histopathological basis to blindly observe all lungs with HE staining and grade them according to the lung injury scoring standard (El-Sherbiny et al, 2021). The lung injury score was calculated as the sum of the score of each indicator.…”
Section: Lung Histopathologymentioning
confidence: 99%